Tecnologia para o controle químico de plantas invasoras - Coltro, Ivan (2017)
Brazilian agriculture plays a very important role in the national economy and improving the production processes is something that is continuously sought. Methods that help the proper management of crops for greater productivity and cost reduction are essential for a more competitive agriculture. The control of invasive plants is among the factors that most influence the profitability of a crop, because if it is carried out in an inefficient way, it can make the activity unfeasible. The use of sensors that automate some of the various processes carried out in the field has been taking hold in modern agriculture and contributing to the record productions currently recorded, but in most cases are inaccessible to the great majority of producers. In this work a prototype was developed that automates the process of controlled application of herbicide, with a cost of 13.53% in relation to the main commercial equipment that perform such function. It is an equipment developed with hardware and free software, which performs the digital capture and processing of images, promoting the identification of invasive plants and localized application of non-selective herbicides. The images are collected by a webcam controlled by the Raspberry card, which also performs the digital processing of these images with the help of Opencv software. The equipment also has a solenoid valve that controls the flow of herbicide. All the construction and tests were carried out in the municipality of Vera Cruz do Oeste, Paraná. The maximum speed obtained in the tests was of 4 km / h, little compared to the 25 km / h of commercial equipment, detecting plants with leaf area with at least 3 cm², a result very similar to the main commercial equipment present in the market. In order to achieve a low operating speed, the equipment proved to be viable in its use, since it can generate profit from the herbicide economy in approximately two years, depending on the area and degree of use of the equipment.